Human dignity and the future of global institutions - Lagon, Mark P.; Arend, Anthony C. (Georgetown University Press, 2014)
The 21st century has witnessed a proliferation of international institutions, including traditional intergovernmental organizations, non-governmental organizations, private sector entities, and other partnerships. The premise of this anthology is that these institutions need a common, animating principle in the service of the person, which is the ultimate end of global politics. The concept of human dignity, the editors claim, serves this purpose and transcends the seemingly intractable conflicts in human rights debates: political rights v. social and economic rights. Conceptually, human dignity rests on two principles: exercising agency to realize one's potential, and recognition by society of one's worth. In light of this formulation of human dignity, the anthology has two purposes: First, contributors will examine the degree to which traditional and emerging institutions are already advancing human dignity as a central mission. Second, in the spirit of developing best practices and prescriptive recommendations, contributors will identify strategies, methods, and modalities to make human dignity more central to the work of global institutions.